Pengaruh Ice Breaking Senam Otak terhadap Kejenuhan Belajar Siswa di Sekolah Dasar - Lili Ramadhanti; Zaka Hadikusuma Ramadan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Boredom is believed to hinder students' learning abilities. When someone feels bored and lacks enthusiasm in carrying out study assignments, this can cause a condition both mental and physical which is called learning boredom. However, at SDN 42 Pekanbaru, there were students who reported feeling physically, mentally and emotionally tired. The aim of this research is to find out to what extent icebreaking can help grade IV students at SDN 42 Pekanbaru overcome their academic boredom. One Group Pretest Posttest Design is the experimental methodology used in this quantitative research. All class IV participants at SDN 42 Pekanbaru were used as the population. Meanwhile, the sample was 33 students of class IV D at SDN 42 Pekanbaru. Because the population was too large, class IV D was used as a representative research sample. In this research, questionnaires and documentation are the methods used to collect data. Two tests form the testing instrument: one for validity and the other for reliability. The normality test and homogeneity test are analysis requirements tests used with the data analysis approach. Based on research findings, this correlation is demonstrated by a normality test which examines data from student boredom questionnaires. The pre-test and post-test data show significant values ​​of 0.200 and 0.109 respectively above 0.05 which indicates that the pre-test data is significant. Ha accepted his decision. Therefore, the results of the data normality test are distributed regularly. Upon receipt of the icebreaker solution, it is determined that a noteworthy effect has occurred. So that fourth grade students at SD Negeri 42 Pekanbaru can overcome learning boredom through Ice Breaking.